High-Performance All-Inorganic Perovskite Tandem Photodetectors With Bi2TeO6 Layer Enabled by Enhanced Dual Pyro-Phototronic Effect for Triple-Encryption Imaging Sensing System with Programmable Logic Gate - Zhao, Yue (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 Wiley‐VCH GmbH.